Illuminating determinants of implementation of non-dispensing pharmacist services in home care: a qualitative interview study - Bø, Karl-Erik; Halvorsen, Kjell H.; Risør, Torsten; Lehnbom, Elin C. (Scandinavian journal of primary health care, 2023)
The results in this study illuminate barriers and facilitators to the implementation of pharmacist services in a home care setting. Existing medication work methods and poor information handover systems are likely to counteract outcomes of the pharmacist services and inflict unfavorable conditions for implementation. Healthcare professionals' perception of increased medication work support and confidence in pharmacist skills suggest innovation acceptability and serve as indicators of implementation success. The identified barriers to improving medication work provide opportunities to develop tailored strategies to enhance the implementation of non-dispensing pharmacist services. Medication errors are leading causes of hospitalization and death in western countries and WHO encourages health care providers to implement non-dispensing pharmacist services in primary care to improve medication work. However, these services struggle to provide any impact on clinical outcomes. We wanted to explore health care professionals' views on medication work to illuminate determinants of the implementation success. The research was designed to inform and adapt implementation strategies for non-dispensing pharmacist services. Semi-structured interview study with nine healthcare professionals. Four Norwegian home care wards. Nine healthcare professionals working at different wards within one home care unit. Determinants of implementation outcomes. Contextual determinants of the implementation process were mainly related to characteristics of the setting such as poorly designed information systems, work overload, and chaotic work environments. The identified barriers question the innovation's appropriateness related to the setting's needs but also provide possibilities for tailoring pharmacist services to local medication work issues. The observable positive effects and the perceived advantage of the pharmacist services are likely to facilitate the implementation process. Our study provided information on contextual elements that influence the implementation process of non-dispensing pharmacist services. Awareness of these factors can help develop strategies to help the organization succeed in in achieving program outcomes.